Fouling-resistant biofilter of an anaerobic electrochemical membrane reactor - Yu, Qilin; Zhang, Yaobin (Nature communications, 2019)
Membrane fouling is a considerable challenge for the stable operation of anaerobic membrane-based bioreactors. Membrane used as a cathode is a common measure to retard fouling growth in anaerobic electrochemical membrane bioreactors (AnEMBR), which; however, cannot avoid the fouling growth. Here we report a strategy using the membrane as an anode to resist membrane fouling in an AnEMBR. Although aggravating in the initial stage, the fouling on the anode membrane is gradually alleviated by the anode oxidation with enriching exoelectrogens to finally achieve a dynamic equilibrium between fouling growth and decomposition to maintain the operation stable. A mesh-like biofilter layer composed of cells with less extracellular polymeric substance (EPS) is formed on the membrane surface to lower the trans-membrane pressure and promote the interception of the anode membrane. The membrane has high electron storage and transfer capacities to accelerate the oxidation of the intercepted fouling materials, especially, the redundant EPSs of the biofilter layer. Membrane use as a cathode is a common measure to retard fouling in anaerobic electrochemical membrane bioreactors, but this cannot avoid the fouling growth. Here the authors report on using membranes as anodes to create equilibrium between fouling and oxidation to maintain stable operation.